1992
DOI: 10.1007/bf03008231
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of auscultation in positioning of double-lumen endobronchial tubes

Abstract: Reliability of auscultation in positioning of double-lumen endobronchial tubes Auscultation is a well-established technique to confirm the position of double-lumen endobronchial tubes (DLTs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 15 publications
(4 reference statements)
2
32
0
2
Order By: Relevance
“…Other studies report the incidence of malpositioning of left-sided DLTs to range from 10-83% (weighted mean, 53%). [1][2][3][4][5]15 One effect of the higher than anticipated incidence of malposition of DLTs is that the number of patients enrolled is generous. Our rather stringent definition of device malposition may be responsible for the high rate of malpositions we report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report the incidence of malpositioning of left-sided DLTs to range from 10-83% (weighted mean, 53%). [1][2][3][4][5]15 One effect of the higher than anticipated incidence of malposition of DLTs is that the number of patients enrolled is generous. Our rather stringent definition of device malposition may be responsible for the high rate of malpositions we report.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that bronchoscopy be used to verify the correct position because the incidence of malpositions is high. [1][2][3][4][5] The major disadvantage of DLTs is the often difficult placement because of the larger diameter; as a consequence, patients often complain of hoarseness or sore throat. 6 There is also a potential for minor laryngeal, tracheal, and bronchial trauma.…”
mentioning
confidence: 99%
“…Different malposition scenarios may be deduced depending on type of DLT (L v. R), intended mainstem to be intubated, DLT lumen occluded and the absence or presence of breath sounds. Although auscultation is an important tool in situations where fiberoptic bronchoscopy is unavailable, studies have shown a large margin of positioning error when it is not used [15][16][17][18]. Fiberoptic confirmation is required for proper positioning of bronchial blockers because they lack basic ergonomic design features that enable blind placement (like curvature or specialized ventilation port configurations of DLTs).…”
Section: Confirming Proper Lung Isolationmentioning
confidence: 99%
“…Auscultation of breath sounds has limited sensitivity and depends on the experience of the listener. [2][3][4][5][6][7][8] Colorimetric end-tidal carbon dioxide detectors are simple to use, inexpensive, and have a high sensitivity and specificity to accurately differentiate between esophageal and tracheal intubation in the patient with good lung perfusion. 9 Vibration response imaging (VRI) is a novel, non-invasive, computer-based technology that measures vibration energy of lung sounds during respiration.…”
Section: éLéments Cliniques : L'imagerie Par Réponse Vibratoire (Vri)mentioning
confidence: 99%